2000
DOI: 10.1007/s002640050008
|View full text |Cite
|
Sign up to set email alerts
|

Supracondylar nailing of distal periprosthetic femoral fractures

Abstract: Seven patients who sustained complex distal femoral fractures above total knee arthroplasties all treated by supracondylar (retrograde) femoral nailing were retrospectively evaluated. All the patients demonstrated uncomplicated postoperative follow-ups and returned to weight bearing between 2 and 3 months after surgery. No delayed healing occurred and alignment of the femur was satisfactory.Résumé Nous avons réalisé une étude rétrospective comprenant sept fractures periprothetiques complexes du fémur distal ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 18 publications
(42 reference statements)
2
14
0
1
Order By: Relevance
“…Ultimately, 29 articles were included in this systematic review. A total of 415 fractures that were treated either nonoperatively (Short et al 1981, Sisto et al 1985, Cain et al 1986, Merkel and Johnson 1986, Culp et al 1987, Bogoch et al 1988, Nielsen et al 1988, Cordeiro et al 1990, Garnavos et al 1994, Moran et al 1996, operatively by conventional non-locking plating techniques (Short et al 1981, Sisto et al 1985, Cain et al 1986, Merkel and Johnson 1986, Culp et al 1987, Bogoch et al 1988, Nielsen et al 1988, Cordeiro et al 1990, Healy et al 1993, Zehntner and Ganz 1993, Garnavos et al 1994, Moran et al 1996, Oschner and Pfister 1999, Weber and Peter 1999, Al-Shawi et al 2002, Wang and Wang 2002, Althausen et al 2003, Bezwada et al 2004, retrograde intramedullary nailing (Culp et al 1987, Garnavos et al 1994, McLaren et al 1994, Weber et al 2000, Wick et al 2001, 2004, Althausen et al 2003, Bezwada et al 2004, Gliatis et al 2005, locked submuscular plating techniques (Kregor et al 2001, Althausen et al 2003, Wick...…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, 29 articles were included in this systematic review. A total of 415 fractures that were treated either nonoperatively (Short et al 1981, Sisto et al 1985, Cain et al 1986, Merkel and Johnson 1986, Culp et al 1987, Bogoch et al 1988, Nielsen et al 1988, Cordeiro et al 1990, Garnavos et al 1994, Moran et al 1996, operatively by conventional non-locking plating techniques (Short et al 1981, Sisto et al 1985, Cain et al 1986, Merkel and Johnson 1986, Culp et al 1987, Bogoch et al 1988, Nielsen et al 1988, Cordeiro et al 1990, Healy et al 1993, Zehntner and Ganz 1993, Garnavos et al 1994, Moran et al 1996, Oschner and Pfister 1999, Weber and Peter 1999, Al-Shawi et al 2002, Wang and Wang 2002, Althausen et al 2003, Bezwada et al 2004, retrograde intramedullary nailing (Culp et al 1987, Garnavos et al 1994, McLaren et al 1994, Weber et al 2000, Wick et al 2001, 2004, Althausen et al 2003, Bezwada et al 2004, Gliatis et al 2005, locked submuscular plating techniques (Kregor et al 2001, Althausen et al 2003, Wick...…”
Section: Resultsmentioning
confidence: 99%
“…Intramedullary fixation does have certain advantages over extramedullary techniques and has demonstrated good short and mid-term results [10,24]. Typically, there is little or no disturbance to soft tissue attachments at the fracture site, and the construct has been demonstrated to have a biomechanical advantage [3].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple techniques have been proposed including: blade plates, dynamic condylar screw and plate, condylar buttress plates [9,25], Rush pins [19], Enders nails [11], and external fixation [22]. More recently, locking plates [1,13] and the retrograde intramedullary locked supracondylar nail have been described [10,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have now shown high success rates with the supracondylar nail in the management of periprosthetic fractures of the distal femur [9][10][11][12][13]. Four studies involving a total of 19 patients showed a 100% union rate with no complications [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment is usually employed for an undisplaced fracture and it involves immobilisation in a brace and nonweight-bearing until the fracture is fully healed [1-3]. Surgical options for a displaced fracture above a well-fixed knee arthroplasty include open reduction and internal fixation using conventional plates [4,5], minimally invasive fixation using locking plates [6][7][8], and retrograde supracondylar nailing [9][10][11][12][13]. However, if the prosthesis is loose then a major reconstruction like revision arthroplasty [14,15], distal femoral allograft [16] or a prosthetic replacement of the distal femur [17] is required.…”
Section: Introductionmentioning
confidence: 99%